Effect of Earning Per Share, Company Size and Institutional Ownership on Stock Return - Tri Ayu Parwati; Hamdy Hadi; Elfiswandi Elfiswandi (UPI YPTK Journal of Business and Economics, 2022)
This study aims to determine all the effects of earnings per share, ownership size, institutional ownership on stock returns. The study used a population of all manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period with 65 sample companies obtained through the round-trip method. This study uses multiple linear regression analysis. The results showed that the variable earning per share partially shows t has a significant effect on stock returns with a significant value. The company size variable partially shows a significant effect on stock returns with a significant value. The institutional ownership variable partially shows a significant effect on stock returns with a significant value. Simultaneously, earnings per share, company size and institutional ownership have a significant effect on stock returns with a significant value.